MODEL DESAIN FLOWMAP RAWAT INAP DIRUMAH SAKIT TYPE B DENGAN INFORMASI KELAS PERAWATAN PASIEN - Puspita, Rahmadani Eka; Parasati, Nadia Indah; Utaminingsih, dkk, Citra (DINAMIKA DOTCOM, 2019)
Implementation of Electronic Medical Records by using flow maps is a mixture of maps and flow charts, which show the movement of objects from one location to another, such as the number of people in migration, the number of items traded, or the number of packages in the network. Flowchart is a chart (chart) that shows flow in a program or system procedure logically. Flowchart is used mainly for communication aids and for documentation. At this stage there is also a need analysis where the needs analysis is an analysis to find out who the users involved in the information system to be built include: [1] Medical record officers (registration, data input, storage), [2] Doctors, [3] Nurse, [4] Admin hospitalized. By using Dreamweaver CS 6 Application, it is expected to make it easier to create a chart and flow of inpatient services at the hospital. In modeling flowmap design inpatient services not only record how to operate now (the process as is), it should be considered how to operate with the potential benefits of introducing information systems that can streamline activities. Keywords : General characteristics of the system, medical record social data, data transfer